THE EFFECT OF JIGSAW STRATEGY IN TEACHING READING OF RECOUNT TEXT (AN EXPERIMENTAL RESEARCH AT THE FIRST GRADE ON MAN 5 BIREUEN): THE EFFECT OF JIGSAW STRATEGY IN TEACHING READING OF RECOUNT TEXT (AN EXPERIMENTAL RESEARCH AT THE FIRST GRADE ON MAN 5 BIREUEN) - SITI SARAH; MUHAMMAD AFRIZAL (Journal of English Education and Social Science, 2021)
The research of the effect of jigsaw strategy in teaching reading of recount text has been done at MAN 5 Bireuen. It was begun from March 9 2021 until March 12 2021. The problems of this research are; does the jigsaw strategy provide a better effect to students reading Score? And to what extent does the jigsaw strategy provide the significance effect to the students reading score. Based on the research problems, there are two purposes of the research, namely; to find out the jigsaw strategy to provide a better effect students reading score and to find out extent the jigsaw strategy provides the significance effect to the students reading score. The scope of this research focused on investigating the use of Jigsaw strategy in the increase of students’ reading score. This research is designed as an experimental research with test consisted of pre-test and post-test as the sole instrument, the data is then analyzed using the formula introduced by Winarsunu to find the mean score and using the paired T-score statistical formula to find the t-value in order to prove the hypotheses. The results of the research on the effect of jigsaw strategy in teaching reading of recount text on 1st grade students of MAN 5 Bireuen showed that there was an increase in the mean score of students from 57,5 (pre-test) to 97,5 (post- test). The increase was also seen in the student category scores where previously they were at the sufficient category (pre-test), increased to the very high category (post-test). The hypothesis which states that there is a significant difference in students' ability in reading recount text before and after the jigsaw technique is applied (H1) is accepted. This can be seen from the t value (8,16) > t-table value (2,07), taking into account the significant level (α) 0.05 or confidence level 95%, the correlation coefficient value 0,26, and the standard deviation value of pre-test 21,37 and post-test 3,98.